2017
DOI: 10.1002/ejp.1145
|View full text |Cite
|
Sign up to set email alerts
|

Higher doses of intraoperative analgesia are associated with lower levels of persistent pain and less analgesic consumption six months after total hip arthroplasty

Abstract: Our study suggests that lower doses of intraoperative analgesia are associated with higher levels of persistent postoperative pain. Persistent pain may be caused by intraoperative nociception, which is likely not adequately suppressed using current clinical standard analgesic measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…In TKA patients with preoperative opioid use, about 18% had increased opioid consumption, corresponding to the well-known risk of persistent or even increased pain after TKA (Beswick et al, 2012). A recent prospective cohort study in THA also demonstrated continued unspecified analgesic use in 32% of patients, as well as a median pain level of 4/10 6 months after surgery (von Dincklage et al, 2018). However, their patients all had general total intravenous anaesthesia, whereas the use of neuraxial anaesthesia has been reported in about 90% of procedures in the departments contributing to our cohort (Bjerregaard et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In TKA patients with preoperative opioid use, about 18% had increased opioid consumption, corresponding to the well-known risk of persistent or even increased pain after TKA (Beswick et al, 2012). A recent prospective cohort study in THA also demonstrated continued unspecified analgesic use in 32% of patients, as well as a median pain level of 4/10 6 months after surgery (von Dincklage et al, 2018). However, their patients all had general total intravenous anaesthesia, whereas the use of neuraxial anaesthesia has been reported in about 90% of procedures in the departments contributing to our cohort (Bjerregaard et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…25 İntraoperatif yeterli analjezi yönetimi santral sensitizasyonu engelleyerek kronik ağrıyı önleyebilir. 26,27 Bu ilişki psikososyal faktörler varlığında bile mevcuttur. Güncel klinik standartlarla uygun anestezi ve analjezi sağlanmadığında PPP'nin intraoperatif nosisepsiyondan kaynaklanması mümkün gözükmektedir.…”
Section: Discussionunclassified
“…Several studies in human medicine have shown that both preoperative pain and acute postoperative pain are correlated with persistent postoperative pain 16–18 . The relation between intraoperative nociception and postoperative pain has been shown in hip surgery on humans.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between intraoperative nociception and postoperative pain has been shown in hip surgery on humans. Titration of perioperative analgesic based on nociception reduces postoperative pain 17,19 . Given these correlations, assessing the presence of a connection between intraoperative nociception and postoperative pain might prove beneficial, by allowing to identify patients with likely higher postoperative analgesic requirements, which could help guide the use of postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%